Real-World Patterns of Utilization and Costs Associated with Second-Generation Oral Antipsychotic Medication for the Treatment of Bipolar Disorder: A Literature Review - Doane MJ (Dove Medical Press, 2021)
Michael J Doane,1 Kristine Ogden,2 Leona Bessonova,1 Amy K O’Sullivan,1 Mauricio Tohen3 1Health Economics and Outcomes Research, Alkermes, Inc., Waltham, MA, USA; 2Evidence, Worldwide Clinical Trials, Morrisville, NC, USA; 3Department of Psychiatry and Behavioral Sciences, University of New Mexico, Albuquerque, NM, USACorrespondence: Leona BessonovaHealth Economics and Outcomes Research, Alkermes, Inc., 852 Winter Street, Waltham, MA, 02451-1420, USATel +1 781 609 6439Email leona.bessonova@alkermes.comObjective: Treatment with second-generation antipsychotics (SGAs) for bipolar disorder, including bipolar I disorder (BD-I), is common. This review evaluated real-world utilization patterns with oral SGAs in the United States (US) for bipolar disorder (and BD-I specifically when reported) and economic burden associated with these patterns.Methods: Structured, systematic searches of MEDLINE®, EMBASE®, and National Health Service Economic Evaluation Database identified primary research studies (published 2008– 2018) describing real-world SGA use in adults with bipolar disorder/BD-I.Results: Among 769 studies screened, 39 met inclusion criteria. Most studies (72%) were analyses of commercial or Medicare/Medicaid claims databases. Patient-related (eg, demographic, comorbidities) and disease-related (eg, mania, psychosis) factors were associated with prescribed SGA. Suboptimal utilization patterns (ie, nonadherence, nonpersistence, treatment gaps, medication switching, and discontinuation) were common for patients treated with SGAs. Also common were SGAs prescribed with another psychotropic medication and SGA combination treatment (use of ≥ 2 SGAs concurrently). Suboptimal adherence and SGA combination treatment were both associated with increased health care resource use (HCRU); suboptimal adherence was associated with higher total direct medical and indirect costs.Limitations: Different definitions for populations and concepts limited between-study comparisons. Focusing on SGAs limits contextualizing findings within the broader treatment landscape (eg, lithium, anticonvulsants). Given the nature of claims data, prescribing rationale (eg, acute episodes vs maintenance) and factors influencing observed utilization patterns could not be fully derived.Conclusion: Despite increased use of SGAs to treat bipolar disorder over the last decade, reports of suboptimal utilization patterns of SGAs (eg, nonadherence, nonpersistence) were common as was combination treatment. Patterns of SGA use associated with additional HCRU and/or costs were suboptimal adherence and SGA combination treatment; economic consequences associated with other utilization patterns (eg, nonpersistence) were unclear. Strategies to improve SGA treatment continuity, particularly adherence, may improve clinical and economic outcomes among people living with bipolar disorder.Keywords: adherence, antipsychotics, economics, mania, mood disorders, prescribing patterns, review